Employing the Technology Acceptance Model to Explore the Trends of Social Media Adoption and its Effect on Perceived Usefulness and Perceived Ease of Use - Manal Alduaij (Journal of Information Technology Management)
The purpose of this research is to explore the social media trend in communication in Kuwait by utilizing the technology acceptance model. Social media has been gaining extraordinary adoption in past years that requires further investigation into user’s adoption habits, the various kinds of social media, and its effect on their perceived usefulness and ease of use of social media. The study consists of a total of 250 participants that were asked to complete a questionnaire in a random sample. Important findings indicate that the highest number of participants uses Facebook, and the second highest number of participants use Twitter. In terms of usage habits, the highest number of participants uses social media for chatting and connecting with family and friends. The second highest number of participants uses social media for reading posts. In terms of perceived usefulness, the highest numbers of participants perceive social media as ‘usefulness’, and the second highest numbers of participants feel that ‘social media is faster’. In terms of perceived ease of use the highest numbers of participants feel that social media is an easy way to communicate, and the second highest numbers of participants feel that social media does not require a lot of effort. In terms of gender it has been evident that females feel higher perceived usefulness and perceived ease of use of social media than males. The study bears theoretical and practical implications that show TAM can be successfully applied to examine social media in the context of Kuwait population. Furthermore, results of this study can be further generalized to neighboring GCC countries as they share similar geographic, economic, cultural, and financial factors.